The effects of family income on test-anxiety and academic achievement among Iranian high school students - Yousefi, Fayegh; Redzuan, Ma'rof; Mansor, Mariani; Juhari, Rumaya; Abu Talib, Mansor (Canadian Center of Science and Education, 2010)
The purpose of this paper is to determine the effect of family income on test-anxiety and academic achievement. The paper is based on a study which was carried out among high school students in Iran. The respondents of the study were 400 high school students (200 males and 200 females) in the age range of 15-19 years old. Instrument used for data collection was Test-Anxiety Inventory (TAI). Statistic analysis of ANOVA was employed to identify the significant differences between family income, test-anxiety and academic achievement. The finding shows that family income significantly affected academic achievement [(F (2) = 19.17, p=.000)] and test-anxiety [(F (2) = 3.92, p=.02)]. Thus, it is recommended that in enhancing academic achievement and test-anxiety in school setting, support strategies such as improve the family income among families by government.